NAVIGATING ATYPICAL OCD PRESENTATIONS: CASE REPORT ON COMPULSIONS WITHOUT OBSESSIONS - Dr. Arslan Mubarik; Dr. Tooba Iqbal; Dr. Muhammad Kamran; Dr. Muhammad Amjad Hussain (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This case study delves into a patient's experience characterized by primary compulsions devoid of obsessions, challenging the traditional diagnostic model of obsessive-compulsive disorder (OCD) commonly accepted in clinical practice. By integrating the criteria outlined in the International Classification of Diseases 11th Revision (ICD-11) for OCD, this narrative underscores the importance of identifying compulsive behaviours motivated by a need for precision or a sense of fulfilment, even in the absence of accompanying obsessions. This refined perspective on diagnosis and management underscores the intricacies and clinical relevance of unconventional OCD presentations.